Interior of Math and Science building, September 1960 (1960)
Interior photo of the Mathematics and Home Economics Building, later the Math and Science Building, featuring the Biological Sciences department. The directory on the wall lists Noble as the Biological Sciences Department Head, and Applegarth, Essig, Fosdick, Hatfield, Hynes, Hoover, Montgomery, Neelands, Pimentel, Rodin, Roest, Thomson, Thurmond, and Wells as the faculty.